Pendampingan Pembuatan Lilin Aromaterapi sebagai Upaya Meningkatkan Kesehatan Mental pada Diaspora Indonesia di Tiongkok - Azis Ikhsanudin; Sucipto Sucipto; Wajiran Wajiran; Lolita Lolita; Leoni Nanda Wulandari (Universitas Muhammadiyah Semarang, 2025)
Mental health is a crucial determinant of overall well-being. In Indonesia, the prevalence of emotional mental disorders among individuals over 15 years old has reached 9.8% of the population. Indonesian diaspora students in China face unique challenges that may increase the risk of mental health decline. This study aimed to describe the mental health status of Indonesian diaspora students in China and to evaluate aromatherapy candle-making activities as a preventive approach to mental health decline. A descriptive qualitative design was employed using a modified and validated version of the World Health Organization-Five Well-Being Index (WHO-5) questionnaire, validated with 10 respondents. Data were collected from Indonesian students through self-administered questionnaires. Additionally, a workshop on aromatherapy candle-making was conducted to explore its potential benefits for mental health improvement. The findings indicated that students experienced negative emotions with a mean score of 3.41 ± 0.95, self-satisfaction with 3.41 ± 0.73, concentration with 3.45 ± 0.80, and body image perception with 3.68 ± 0.95. Most participants expressed interest in aromatherapy candles, perceiving them as beneficial for mental relaxation and emotional well-being. Indonesian diaspora students in China demonstrated tendencies toward feelings of loneliness, hopelessness, anxiety, and depression. Aromatherapy candle-making activities provided a promising alternative approach to mental relaxation, although further research is needed to determine their effectiveness in improving overall mood and mental health.